Regional decentralization of mathematics curriculum in primary and secondary Spanish education during the nineties - Modesto Sierra; Carmen López Esteban (Enseñanza de las Ciencias, 2012)
The 1978 Spanish Constitution strengthened the Spanish Autonomous Communities. Articles comprehended in this Constitution foresaw the assumption of educative obligations by the Autonomies (Spanish regional governments). However, this assumption was not effective until 1990 with the enactment of the LOGSE (Spanish acronym for General Regulation Law of Educative System). Since then the first autonomic curriculum developments were established. This study conducts a comparative analysis among mathematics curriculum developments for Compulsory Education (from 6 to 16-year olds) in several Autonomous Communities.